Influence of Market Penetration Strategy on Growth of Restaurants in Nairobi County - Gikunda, Muguna Juliano; Muchai, Peter; Muema, Wilson (International Journal of Professional Practice, 2023)
Failure of application of market penetration strategy is the lead cause of poor growth of restaurants across Nairobi County, specific adaptation of this marketing strategy can create advantage over the larger market; adjust the price levels; increase rate of consumption; take competitors customers; or convert nonusers of the product or service. Out of desperation, managers stuck to non-traditional methods of operation without adapting to the current changes in business environment to improve efficiency and effectiveness. However, there is minimal data in Kenya and Nairobi County to help managers penetrate new markets. The objective of this study was to determine the perceived influence and possible effect of market penetration strategy on restaurant growth in Nairobi County. Descriptive survey was utilized to enable reveal the underlying problem in restaurant growth. Purposive sampling technique was used to carry out the census. Data was obtained from 30 respondents (food and beverage managers) using questionnaires administered through drop-and-pick method. It was cleansed, coded and manually keyed in SPSS version 26, then summarized using frequency and percentages and presented using tables and charts. Results indicated a significant association between market penetration strategy and the restaurant growth in Nairobi County. Factors found to have strong influence on market penetration were; sales promotions 18(78.2%); free trial offers and give-a ways 18(78.222%); credit terms on products or services provided 19(82.6%); PR strategies of marketing 20(86.9%); mail or telemarketing strategies 21(91.3%); and bought a competitor company or restaurant 19(82.6%); decision generated from Boston Matrix to decide whether the product or service is worthy continued investment or must be disregarded 20(86.9%). Market penetration strategy was found to be statistically significant and positively related to restaurant growth Y(β2 =0.766, P=.001). The study concludes that market penetration strategy is statistically significant in assessing the restaurants’ growth.